Investigating the role of iron status in the development of coeliac disease: a Mendelian randomisation study - Isabel A Hujoel; Margaux Louise Anna Hujoel (BMJ Open Gastroenterology)
Objective The environmental trigger behind the increasing prevalence of coeliac disease is not known. One suggested cause is iron deficiency, which is common in coeliac disease. We aimed to evaluate this possible association with Mendelian randomisation (MR), which under certain assumptions can suggest a causal relationship.Design We conducted a two-sample MR study examining the relationship between single nucleotide polymorphisms (SNPs) associated with iron status and the presence of coeliac disease. The SNPs were drawn from a meta-analysis of three genome-wide association studies (GWAS). The association between these SNPs and coeliac disease was assessed using GWAS summary statistics from the UK Biobank. This consists of 336 638 white British individuals, 1855 with coeliac disease. We performed an MR Egger test for pleiotropy and assessed the plausibility of the assumptions of MR to evaluate for possible causality.Results There were four SNPs strongly associated with systemic iron status. These were not associated with known risk factors for coeliac disease. All four SNPs were available in the UK Biobank coeliac disease summary statistics. Harmonising exposure and outcome associations, we found that higher iron status was negatively associated with risk of coeliac disease (OR per 1 SD increase in serum iron: 0.65, 95% CI 0.47 to 0.91). Leave-one-out analyses had consistent results, and no single SNP drove the association. All three assumptions of MR appeared plausible.Conclusion We found that genetically lower iron levels were associated with an increased risk of coeliac disease. Our findings highlight a potential opportunity for coeliac disease prevention.